Diplomatic Ties between the Ottoman Empire and the Malay Sultanate from the 14th to the 19th Centuries - Ismail, Syaimak; Islam, Muhammad Saiful; Mohamad Akhir, Noor Syahidah; Abdul Rahman, Azhar (Journal of Al-Tamaddun, 2024)
Malaya began its relationship with the Ottoman Turkish Empire in the 15th century, during the time of the Melaka-Sultanate. This relationship continued even after the arrival of colonialists and the fall of the Ottoman Turkish Empire. At first, their relations were focused on politics and economics. These two kingdoms were considered to be the powerful Islamic forces that influenced Europe and Asia. The Sultan of Melaka visited Turkey several times to strengthen their relationship and even took an oath of allegiance to the Ottoman Turkish Empire, promising to defend Islam in Asia. After the fall of Melaka, the Ottoman Turkish Empire provided war aid through Aceh to help Melaka regain control of the seized kingdom. The Ottoman Turkish Empire also influenced the Malay community’s thinking and struggle to resist colonialism in the 18th century. The Malay community even took the Ottoman Turkish Empire as a model for freeing Malaya from Western threats. This paper will examine the initial relationship between the Melaka Malay Kingdom and the Ottoman Turkish Empire, particularly from a political perspective, and the type of influence that catalysed the Malays’ spirit to continue to rise and defend Malaya from external threats. This research will focus on document analysis and descriptive writing methods. The relationship between Malaya and the Turkish Government lasted until the Islamic caliphate fell in 1923. Furthermore, Ottoman Turkey was a significant Islamic government that the Malays expected to obey, as it acted as a power that was always concerned with Islam and the country as an Islamic state.